My Literary Passions - Howells, William Dean, 1837-1920 (Salt Lake City, UT : Project Gutenberg, 2004)
"My Literary Passions" by William Dean Howells is a memoir and literary exploration likely written in the late 19th century. The book presents a vivid reflection on Howells$1 (Bliterary loves and the authors who influenced him throughout his life, serving as both personal reminiscence and broader cultural commentary on reading and literature. At the start of the work, the author sets the stage by recounting his early literary experiences and the familial influences that shaped his reading habits. He reflects on the significance of his childhood bookcase and the many books that inspired him, including works by poets like Goldsmith, Cervantes, and Irving. Howell's writing is imbued with nostalgia as he shares anecdotes about his life intertwined with his reading journey, conveying his passion for literature while hinting at the evolution of his literary tastes and influences over time. The opening portion establishes a strong personal connection to literature, suggesting that the subsequent chapters will deepen this exploration of Howells$1 (Bliterary passions and the development of his identity as a reader and writer. (This is an automatically generated summary.)s
The Bookcase at Home -- Goldsmith -- Cervantes -- Irving -- First Fiction and Drama -- Longfellow's "Spanish Student" -- Scott -- Lighter Fancies -- Pope -- Various Preferences -- Uncle Tom's Cabin -- Ossian -- Shakespeare -- Ik Marvel -- Dickens -- Wordsworth, Lowell, Chaucer -- Macaulay -- Critics and Reviews -- A Non-literary Episode -- Thackeray -- "Lazarillo De Tormes" -- Curtis, Longfellow, Schlegel -- Tennyson -- Heine -- De Quincey, Goethe, Longfellow -- George Eliot, Hawthorne, Goethe, Heine -- Charles Reade -- Dante -- Goldoni, Manzoni, D'azeglio -- "Pastor Fido," "Aminta," "Romola," "Yeast," "Paul Ferroll" -- Erckmann-chatrian, Bjorstjerne Bjornson -- Tourguenief, Auerbach -- Certain Preferences and Experiences -- Valdes, Galdos, Verga, Zola, Trollope, Hardy -- Tolstoy
Release date is 2004-10-22
Produced by David Widger
Keywords: Literature -- History and criticism